4x-6(x+11)=-48

Simple and best practice solution for 4x-6(x+11)=-48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-6(x+11)=-48 equation:


Simplifying
4x + -6(x + 11) = -48

Reorder the terms:
4x + -6(11 + x) = -48
4x + (11 * -6 + x * -6) = -48
4x + (-66 + -6x) = -48

Reorder the terms:
-66 + 4x + -6x = -48

Combine like terms: 4x + -6x = -2x
-66 + -2x = -48

Solving
-66 + -2x = -48

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '66' to each side of the equation.
-66 + 66 + -2x = -48 + 66

Combine like terms: -66 + 66 = 0
0 + -2x = -48 + 66
-2x = -48 + 66

Combine like terms: -48 + 66 = 18
-2x = 18

Divide each side by '-2'.
x = -9

Simplifying
x = -9

See similar equations:

| x^2+16x+16=4x-5 | | x+23,2/11=25 | | 6x+4y=13 | | -92=4+8x | | x+23[2/11]=25 | | 12+1/5m=20 | | 6t+5/9t-5=2t+7/3t-7 | | 6x+4(x-3)=13 | | 92x=883.2 | | 2X-6=3X+7 | | x=150+0.85(x) | | w-147.67=144.67 | | 3/5x21=3x | | .3333p+7=12-.6666p | | (2x^2)/(0.8-x^2)=53.3 | | 3/5+3=21x | | z/325=7 | | z/23=6 | | 1/9p=5/6 | | x=200+0.8(x) | | -5(X-4)+8X=6X-2 | | -6y-9=-3(y+9) | | x+65=50+75 | | 10/27=5/9t | | z^23=6 | | 18y-6=8y-70 | | 50+75=x+65 | | 5(X+4)/6=2X-5 | | 0.2x+1-2=0.5 | | x+(.01x)=15000 | | D=7/3(m-76) | | 2x/2-3x-1=0 |

Equations solver categories